Comparative evaluation of the effects of xylitol and sugar-free chewing gums on salivary and dental plaque pH in children - Shikhar Kumar; Suma H. P. Sogi; K R Indushekar (Wolters Kluwer Medknow Publications, 2013)
This research paper primarily focuses on the importance of use of xylitol among school children. Purpose: The purpose of this paper is to evaluate the salivary and dental plaque pH changes after consumption of sugared and sugar-free (xylitol) chewing gums in children. Materials and Methods: A total of 30 school children were selected for this study and were divided into two equal groups and given both chewing gums for the experiment. Results: Children consuming the sugar-free (xylitol) chewing gum showed a marked increase in the pH of saliva and plaque when compared to their counterpart. All these values had a significant difference of P ≤ 0.0001. Conclusion: Xylitol is a safe all-natural sweetener which helps to reduce tooth decay. It plays a unique role in preventive strategies for better health.